Relationship between Distinct African Cholera Epidemics Revealed via MLVA Haplotyping of 337 Vibrio cholerae Isolates - (:unkn) unknown (My University, 2015)
Background Since cholera appeared in Africa during the 1970s, cases have been reported on the continent every year. In Sub-Saharan Africa, cholera outbreaks primarily cluster at certain hot-spots including the African Great Lakes Region and West Africa. Methodology/Principal Findings In this study, we applied MLVA (Multi-Locus Variable Number Tandem Repeat Analysis) typing of 337 Vibrio cholerae isolates from recent cholera epidemics in the Democratic Republic of the Congo (DRC), Zambia, Guinea and Togo. We aimed to assess the relationship between outbreaks. Applying this method, we identified 89 unique MLVA haplotypes across our isolate collection. MLVA typing revealed the short-term divergence and microevolution of these Vibrio cholerae populations to provide insight into the dynamics of cholera outbreaks in each country. Our analyses also revealed strong geographical clustering. Isolates from the African Great Lakes Region (DRC and Zambia) formed a closely related group, while West African isolates (Togo and Guinea) constituted a separate cluster. At a country-level scale our analyses revealed several distinct MLVA groups, most notably DRC 2011/2012, DRC 2009, Zambia 2012 and Guinea 2012. We also found that certain MLVA types collected in the DRC persisted in the country for several years, occasionally giving rise to expansive epidemics. Finally, we found that the six environmental isolates in our panel were unrelated to the epidemic isolates. Conclusions/Significance To effectively combat the disease, it is critical to understand the mechanisms of cholera emergence and diffusion in a region-specific manner. Overall, these findings demonstrate the relationship between distinct epidemics in West Africa and the African Great Lakes Region. This study also highlights the importance of monitoring and analyzing Vibrio cholerae isolates.
Keywords: African Research